Administration of vitamin D3 induces CNPase and myelin oligodendrocyte glycoprotein expression in the cerebral cortex of the murine model of cuprizone-induced demyelination - Mashayekhi, Farhad; Salehi, Zivar (Folia Neuropathologica, 2016)
In the central nervous system (CNS) the main proteins of myelin are proteolipid protein (PLP), myelin basic protein (MBP), myelin oligodendrocyte glycoprotein (MOG) and CNPase. Myelin oligodendrocyte glycoprotein is a minor component of the myelin sheath, but is an important autoantigen linked to the pathogenesis of multiple sclerosis (MS). CNPase is expressed exclusively by oligodendrocytes in the CNS, and the appearance of CNPase seems to be one of the earliest events of oligodendrocyte differentiation and myelination. In this study the effects of vitamin D on total protein concentration, CNPase and MOG expression in the cerebral cortex of the murine model of cuprizone-induced demyelination was investigated. The mice were treated by cuprizone for five weeks in order to induce demyelination. The mice were then divided into 3 groups. The first group was injected intraperitoneally (IP) with vitamin D diluted in olive oil in the amount of 5 µg/kg/daily body weight. The second group (SHAM) was injected IP with olive oil and the third group was left without any injection as the control group (n = 11 for each group). After five weeks the mice were killed and the cerebral cortex was collected and the expression of CNPase and MOG was studied by Western blot. Total protein concentration in the vitamin D injected, SHAM and control groups were 0.918 ± 0.003, 0917 ± 0.004 and 0.916 ± 0.004 g/l, respectively (p > 0.05). However, a significant increase in the MOG and CNPase expression was seen in vitamin D injected group as compared to SHAM and control groups. It is concluded that vitamin D plays a role in the process of remyelination by increasing MOG and CNPase expression in the cortex.